2012
DOI: 10.1007/s10924-012-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose from Simple and Low Cost Production Media by Gluconacetobacter xylinus

Abstract: Bacterial cellulose pellicles were produced by Gluconacetobacter xylinus using non conventional low-cost carbon sources, such as glycerol remaining from biodiesel production and grape bagasse, a residue of wine production. The carbon sources assayed showed their suitability for microbial cellulose production, with relatively high production values such as 10.0 g/l for the culture medium with glycerol from biodiesel as carbon source and corn steep liquor as nitrogen source; and 8.0 g/l for the culture medium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(119 citation statements)
references
References 54 publications
5
108
2
4
Order By: Relevance
“…SEM image of the BC paper sheet produced from TMCSL medium as shown in figure (2) is characterized by ultrafine three dimensional interwoven network of cellulose nanofibers in the range of 29-72 nm with plenty of connected pores which have different diameters. The results are in agreement with (Vazquez et al, 2013) where BC nanofibers produced by Gluconacetobacter Xylinus on Hestrin Schramm media containing grape bagasse and glycerol for 14 days were in the range of 30-80 nm and with (Cheng et al, 2017) who reported that BC nanofibers produced by Acetobacter xylinum on media containing bagasse hydrolysateas carbon source for 10 days at 30 o C were in the range of 30-80 nm. The FT-IR Spectroscopy was used to indicate the peaks of the BC sheet which are attributed to different functional groups found on native cellulose.…”
Section: Figure 1:-phylogenetic Tree Of Acetobacter Pasteurianus Basesupporting
confidence: 90%
See 1 more Smart Citation
“…SEM image of the BC paper sheet produced from TMCSL medium as shown in figure (2) is characterized by ultrafine three dimensional interwoven network of cellulose nanofibers in the range of 29-72 nm with plenty of connected pores which have different diameters. The results are in agreement with (Vazquez et al, 2013) where BC nanofibers produced by Gluconacetobacter Xylinus on Hestrin Schramm media containing grape bagasse and glycerol for 14 days were in the range of 30-80 nm and with (Cheng et al, 2017) who reported that BC nanofibers produced by Acetobacter xylinum on media containing bagasse hydrolysateas carbon source for 10 days at 30 o C were in the range of 30-80 nm. The FT-IR Spectroscopy was used to indicate the peaks of the BC sheet which are attributed to different functional groups found on native cellulose.…”
Section: Figure 1:-phylogenetic Tree Of Acetobacter Pasteurianus Basesupporting
confidence: 90%
“…Acid whey which is the liquid fraction remains from the cheese manufacture process from milk has been used as a carbon source or a nutrient medium as it contains many valuable nutritional components like 940 lactose, amino acids, many minerals and some group B vitamins as reported by (Jozala et al, 2015;Swanporsi et al, 2014). Corn steep liquor is the by-product obtained from the production of starch from corn also has been used as alternate nitrogen source in the culture medium as it contains some essential amino acids, few carbohydrates, some vitamins and mineral salts which are essential to most of the bacteria as mentioned by (Rani et al, 2011;Vazquez et al, 2013). Costa et al (2017) reported that using CSL as an alternative nitrogen source in the medium caused an increasing in the yield of the cellulose as it contains lactate which induces the production of BC.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…The crystallinity index (CI) of produced BC was determined using the following equation (Vazquez et al 2013 where I200 corresponds to the maximum intensity of the lattice diffraction, and I2θ corresponds to the intensity of the peak at 2θ = 18°, which accounts for the amorphous part of cellulose. The intensity of the peaks was measured as the maximum value obtained for the peak taking into account a baseline.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…The results corresponded to 66.5% of bagasse hydrolysate and 70.3% of the glucose. Such behavior could be ascribed to the small amount of residual inhibitors in the culture medium, which resulted in the hydrogen bonding between the cellulose glucan chains, and there was little reduction in the crystallinity index (Vazquez et al 2013;. …”
Section: Effects Of Dosage Of Activated Carbon On the Detoxification mentioning
confidence: 99%
See 1 more Smart Citation